Direct Comparison between Brachial Pressure Obtained by Oscillometric Method and Central Pressure Using Invasive Method - Park, Sang-Ho; Lee, Seung-Jin; Kim, Jae Yun; Kim, Min Jeong; Lee, Ji Yeon; Cho, A-Ra; Lee, Hyeok-Gyu; Lee, Se-Whan; Shin, Won-Yong; Jin, Dong-Kyu (Soonchunhyang medical science, 2011)
Objective: The importance of central blood pressure evaluation for cardiovascular risk stratification has been emphasized. The aim of this study is to evaluate whether brachial blood pressure obtained by the oscillometric method accurately reflects central blood pressure. Methods: The subjects consisted of 84 consecutive patients with suspected coronary artery disease who underwent cardiac catheterization. Central blood pressure was invasively measured in the origin of the left subclavian artery by using the fluid-filled system,and at the same time, brachial blood pressure in the left upper arm was measured by the oscillometric method. Results: No significant difference was found between central systolic pressure and brachial systolic pressure (144.49±18.84 mmHg vs. 142.44±14.96 mmHg, P=0.063). Bland-Altman analysis accounted for only a small bias of +2.25 mmHg, and the limits of agreement were 24.15 mmHg and -19.65 mmHg. Central diastolic pressure was significantly lower than brachial diastolic pressure (75.80±8.74 mmHg vs. 86.70±10.48 mmHg, P<0.001). Bland-Altman analysis showed a significant bias of -5.45 mmHg, and the limits of agreement were 2.83 mmHg and -13.73 mmHg. Conclusion: These results indicate that central systolic pressure can be directly estimated from brachial systolic pressure using the noninvasive oscillometric method and observed biases seem to remain within the practical range. However, use of the brachial diastolic pressure and pulse pressure measured by the noninvasive oscillometric method is doubtful in clinical practice because of their large biases. KCI Citation Count: 0